2016
DOI: 10.3906/vet-1507-3
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of Schmallenberg virus in Turkey, 2013

Abstract: Schmallenberg virus (SBV) infection emerged in European domestic and wild ruminants in 2011. There is very limited information about the characterization of SBV isolates and the epidemiology of its infections in the rest of world, except for in European countries. We investigated the circulation of SBV in cattle herds in Central Anatolia, Turkey, in 2013. A total of 180 whole-blood samples were analyzed using real-time RT-PCR. The presence of SBV RNA was detected in 6 (3.3%) samples. For phylogenetic analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…Schmallenberg virus (SBV) is a emerge viral disease in ruminants worldwide and Transmitted through the arthropods. it Classified to the Orthobunyavirus genus, family Bunyaviridae, infected animal suffered Increase body temperature, loss of appetence, drop of milk, diarrhea and loss of body conditions (19). In this study the prevalence of schmallenberg virus antibodies in imported calves using ELISA showed that total percentage of infection was 21% (84 from 400 samples), many serological studies recorded the schmallenberg virus antibodies in cattle in different countries with differences in percentage of infection (20) recorded 56.6% of cattle was infected with virus in Ethiopia using cELISA, while (11) investigate the antibodies of the virus in Netherland using virus neutralization test and the result showed the 72.5% of cattle was infected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schmallenberg virus (SBV) is a emerge viral disease in ruminants worldwide and Transmitted through the arthropods. it Classified to the Orthobunyavirus genus, family Bunyaviridae, infected animal suffered Increase body temperature, loss of appetence, drop of milk, diarrhea and loss of body conditions (19). In this study the prevalence of schmallenberg virus antibodies in imported calves using ELISA showed that total percentage of infection was 21% (84 from 400 samples), many serological studies recorded the schmallenberg virus antibodies in cattle in different countries with differences in percentage of infection (20) recorded 56.6% of cattle was infected with virus in Ethiopia using cELISA, while (11) investigate the antibodies of the virus in Netherland using virus neutralization test and the result showed the 72.5% of cattle was infected.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the animals suffer from diarrhea, depression, fever recorded high prevalence compare with healthy once, several studies included the clinical signs in cattle which infected with SBV (19) how said that there is mild clinical signs such as reduced milk yield or increase temperature but abortion is considered while (2) recorded mild increase of body temperature, diarrhea and a decrease in milk production, other studies (20) showed that the SBV cause Reproductive disorders including abortion, and metritis, other researchers indicate that calves which SBV positive were arthrogryposis, brachygnathia inferior, torticollis, kyphosis, lordosis, scoliosis, and muscle hypoplasia (24).…”
Section: Discussionmentioning
confidence: 99%
“…(2)'nın bildirdiği pozitiflik değerlerin-den düşük bulunmuş; aynı çalışmada diğer hayvan türle-rinde saptanan seroprevalans değerlerinin de (sığırlarda %39.8, keçilerde %2.8, mandalarda %1.5) bu çalışmada elde edilen koyun değerlerinden yüksek olduğu gözlen-miştir. İç Anadolu Bölgesi'nde sığırlarda gerçekleştirilen başka bir çalışmada seroprevalans değeri %24.1 olarak belirlenmiştir (23). Bu çalışmada koyunlarda saptanan seroprevalans değerlerinin ülkemizde sığırlarda belirlenen seroprevalans değerlerinden düşük olması, Wernike ve ark.…”
Section: Tartışma Ve Sonuçunclassified
“…Schmallenberg virus (SBV; Bunyavirales, Peribunyaviridae , Orthobunyavirus ) was discovered in 2011 in Germany, 13 and epidemiologic studies reveal that SBV is present in many European countries, including Turkey. 4,19 SBV has a 3-segment RNA genome consisting of small (S; 830 nt), medium (M; 4,415 nt), and large (L; 6,864 nt) segments. 13…”
mentioning
confidence: 99%